Chemotherapy-Induced Anemia and Oncologist Perception on Treatment: Results of a Web-Based Survey. Issue 1 (January 2013) - ,
Aims and background: Anemia prevalence and incidence in chemotherapy-treated patients is high. Erythropoiesis-stimulating agents (ESAs) are frequently employed in the management of chemotherapy-induced anemia. However, other treatments such as red blood transfusion or iron supplementation are normally used. Recent international guidelines raised some concern about ESAs employment with a possible impact in chemotherapy-induced anemia management and changes in clinical practice behavior. Methods: To evaluate opinions about chemotherapy-induced anemia clinical management preference, the Associazione Italiana Oncologia Medica (AIOM) Lombardy section coordinators sent via email a 12-item questionnaire about their knowledge on CIA and usual therapeutic strategies to manage this adverse event to AIOM Lombardy onco-hematologist members. Results: From January 2011 to March 2011, 81 questionnaires were collected with an approximated share of 30%. The survey was completed mainly by oncologists (91%) aged 35–50 years (50%). Chemotherapy-induced anemia was considered to have clinical impact in changing cancer therapeutic strategy by nearly 60% of the respondents. ESAs were administered largely (80%) with concomitant iron supplementation in 52%; 38% jointly used blood transfusion as part of the therapy. Nearly 20% of those who replied correctly employed transferrin saturation levels as a marker to guide iron supplementation. Physician prescribers strictly followed the guidelines to start and stop ESAs even if 14% were negatively influenced by new ASCO recommendations. ESA biosimilars were considered future substitutes of originators in 45% of the cases. Conclusions: Chemotherapy-induced anemia was perceived as an adverse event with a mild impact on clinical practice. ESAs were largely employed, however the number of transfusions and lack of employment of markers of iron depletion suggested that adherence to guidelines could be theoretically met but with some discordances regarding the most appropriate strategies in daily clinical practice.